Cancer Prediction Based On Data Mining Using Decision Tree Algorithm - Loh, Kin Ming (2022)
One of the most fatal diseases nowadays in the world will be cancer. Some hereditary factors, environmental variables, and today's contemporary lifestyle all contribute to the development of cancer. In some developed countries, cancer has become the leading cause of mortality. To prevent cancer mortality, early detection of cancer is the most efficiency way to approach. Cancer diagnosis is hard, but if it is found early enough, it may be treated. Many studies have been conducted in order to predict cancer. Different data mining method has showed up with its related algorithms were adopted by different research. Each work has some shortcomings like lack of intelligent prediction and an inefficient structure which eventually prompted me to take on this subject and develop a cancer prediction system. I have proposed a research which is cancer prediction using data mining. The main aim of this research is to provide a helpful information and prediction towards cancer not only for the public, but also for the science industry and related industry.